(untitled) (Journal of the College of Basic Education, 2026)
The aim of this research is to shed light on the role of public administration in promoting financial inclusion and how this role contributes to achieving social justice in Iraq. This research relies on a descriptive and analytical approach, which enables the study of the administrative phenomenon of interest through its statistical description and interpretation. With the aim of reaching an accurate scientific understanding of the nature of the relationship between public administration, financial inclusion, and social justice in the Iraqi context, the research reached many results, including a high level of public administration performance in Iraq, the presence of an average level of implementing financial inclusion in Iraq, and the presence of an average level of achieving social justice in Iraq from the point of view of the study sample members. With the aim of reaching an accurate scientific understanding of the nature of the relationship between public administration, financial inclusion, and social justice in the Iraqi context, the research reached many results, including a high level of public administration performance in Iraq, the presence of an average level of implementing financial inclusion in Iraq, and the presence of an average level of achieving social justice in Iraq from the point of view of the study sample members.